Optimalisasi Infrastruktur Wudhu Masjid Ghoiru Jami Nurul Amin sebagai Upaya Peningkatan Sanitasi dan Keselamatan Jamaah - Handayasari, Indah; Sepriyanna, Irma; Rostianti, Susy F; Fitriani, Yessy (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service program was initiated due to inadequate sanitation and safety conditions of the ablution facilities at Masjid Ghoiru Jami Nurul Amin. Limited space, insufficient water capacity, poor drainage, and the absence of gender-separated areas resulted in user discomfort. The program aimed to improve the quality of the ablution infrastructure through a participatory Service-Learning approach. The methodology included technical surveys, engineering design planning, cost estimation, supervised construction, and user satisfaction evaluation using a Likert scale involving 40 respondents. The results indicate a significant improvement in facility performance, including an expansion of the functional area from 18 m² to 32 m², an increase in water storage capacity from 1,000 liters to 3,000 liters, and an increase in average user satisfaction from 2.22 to 4.50 (103%). The revitalization effectively enhanced sanitation standards, safety, and user comfort